PENERAPAN METODE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA ANAK SEKOLAH DASAR DALAM PEMELIHARAAN KESEHATAN GIGI DAN MULUT DI SDN CEMPAKA PUTIH TIMUR 03 JAKARTA - Putri Yulia Ningsih, Eka (AKG Puskesad, 2023)
Background: Dental and oral health education is one of the efforts to improve health in children. Dental and oral health in Indonesia is still very poorly applied in elementary school environments. Many dental health problems are found in elementary school children because of the structure of teeth in childhood in the type of teeth that are still a mixture, namely between baby teeth and permanent teeth which are very susceptible to caries. Government efforts in improving the quality of dental and oral health through dental health promotion. One effective effort with the application of student team achievement division (STAD) is a cooperative learning method carried out using group methods. Objective: Know the application of the Student Team Achievement division Team (STAD) method in elementary school children in maintaining oral and dental health. Method: This type of research uses a descriptive method that is used to solve or answer problems faced in the current situation. The sample in this study used purposive sampling techniques totaling 36 respondents who met the criteria for inclusion and exclusion in the population and were divided into two groups for the application of the Student Team Achievement Division method. Results: This study used a paired t-test parametic test. The results of the analysis show that the application of the Student Team Achievement Division (STAD) method on Asymp.Sig. (2-tailed) : 0.000 (p>0.005). statistical test results average the difference in the application of the Student Team Achievement Division method before and after is 12.00. Conclusion: There is a difference in knowledge improvement between before and after the application of the Student Team Achievement Division method.